A Bibliometric Analysis of 4Cs Implementation in Teaching and Learning - Marlina Ummas Genisa; Wulandari Saputri; Septi Meliani Hartato; Reno Esa Mahendra (Jurnal Penelitian Pendidikan IPA, 2024)
Bibliometric research offers a thorough picture of its study subject, identifies gaps in the field, encourages the development of new ideas, and makes contributions to research disciplines that are related to it. For the purpose of providing in-depth information regarding the development and direction of 4C research in the educational setting, this research was carried out. After doing a search for scientific publications on the 4Cs issue that were indexed by Scopus, the research was carried out using a bibliometric analysis approach. A total of 81 articles that were related to the topic were acquired, and these articles were then examined using Vos Viewer and visualized. 21st-century talents is the keyword that appears the most frequently in relation to the 4Cs, as indicated by the findings of the research, which shows that it appears 25 times. Research that has been carried out over the course of the past five years reveals an increase that is expected to continue to increase in the years to come. The utilization of digital learning environments is the research potential that can be created in relation to the 4C